Challenges And Opportunities in Sharia Bank Development in Indonesia, A Literature Review - Esaputra, Ahmad Baihaqi (Cattleya Darmaya Fortuna, 2024)
Sharia bank development in Indonesia has a positive trends, however the development of Sharia bank still far below the development of the conventional bank. Despite the muslim population are the largest in Indonesia but it still not maximized yet for developing Sharia bank. This research using bibliometrics approach from the previous study from 2003-2023 and continuing with systematic literature review for examine the challenges and opportunities in developing Sharia bank in Indonesia. This Research find the most productive institution, authors and most influence journal and articles, there is a challenges and opportunity that changes periodically according to the condition of socioeconomics, but the main challenges and opportunities in developing sharia bank in Indonesia are sharia compliance, productivity, profitability, solvability, bank management, customer behavior and market competition. The result from this study conduct a lesson and strategies that can be utilized for developing Sharia bank, and can help the future researcher to do further study about critical and populer issues in Sharia bank development topics.